Giacomo Antonio Marta: Antipapal Lawyer and English Spy, 1609-1618 - Grendler, Paul F. (The catholic historical review, 2007)
Giacomo Antonio Marta (1557/58-1629) of Naples was a distinguished legal scholar and professor at several Italian universities. His education, warm feelings for the Jesuits, and career should have made him a papal defender in an era of church-state jurisdictional conflict. But in a legal work of 1609 he limited papal temporal rights and became a spy for James I of England. He published an anonymous pamphlet which excoriated the papacy for its alleged sins and called for a general council to depose Paul V. But not even his enemies believed that he was anything but a Catholic.